2018
DOI: 10.1590/1980-5373-mr-2017-0599
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Radiopacity of Calcium Aluminate Cement Based Blends

Abstract: The radiopacity of CAC-based compositions containing additives (ZnO, Ag and Bi 2 O 3 ) was evaluated by optical density measurements, cold crushing strength, apparent porosity, pore size distribution, in vitro apatite-formation ability (bioactivity) and cell viability. The bioactivity was assessed via pH and calcium concentration measurements in simulated body fluid (SBF) for samples previously treated or not with sodium silicate (SS) solution. The surface of the samples after treatment was analyzed by scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…According to the previous studies 18,25,26 the significant drop in apparent porosity observed after treatment with SBF can be explained by the presence of precipitates on the surface of the materials. Thus, the same effect should take place for the plain CH and blends with BG in the present work.…”
Section: Resultsmentioning
confidence: 84%
“…According to the previous studies 18,25,26 the significant drop in apparent porosity observed after treatment with SBF can be explained by the presence of precipitates on the surface of the materials. Thus, the same effect should take place for the plain CH and blends with BG in the present work.…”
Section: Resultsmentioning
confidence: 84%
“…Besides that, other CAC-based blends, 15:10 wt% ZnO-Bi 2 O 3 , also presented apatite precipitation on its surface which filled in the pores on the solid surface. This composition showed suitable for clinical purposes in relation to radiopacity (Oliveira et al 2018). Other studies also show the biofilm formation analysis of blend of CAC with zirconia (Vasconcellos et al 2020).…”
Section: Introductionmentioning
confidence: 67%
“…Calcium aluminate-based cement (CAC) represents a promising alternative since it exhibits favorable physicochemical characteristics such as its thermal coefficient of and chemical composition similar to the tooth and human bone 9 – but also due to the bioactivity, i. e., its ability to form a biologically active apatite layer upon exposure to body fluids 10 12 . This property, also observed in calcium silicate-based cements such as mineral trioxide aggregate (MTA), involves the calcium release and the pH raise in the milieu 13 , 14 and is considered essential for the stimulating effect of these materials on cellular events that form mineralized tissues 13 .…”
Section: Introductionmentioning
confidence: 99%